Environmental Engineering Dictionary of Technical Terms and Phrases : English to Mandarin and Mandarin to English. - Hopcroft, Francis J. (Momentum Press, 2016)
This reference manual provides a list of approximately 300 technical terms and phrases common to Environmental and Civil Engineering which non-English speakers often find difficult to understand in English. The manual provides the terms and phrases in alphabetical order, followed by a concise English definition, then a translation of the term in Mandarin and, finally, an interpretation or translation of the term or phrase in Mandarin. Following the Mandarin translations section, the columns are reversed and reordered alphabetically in Mandarin with the English term and translation following the Mandarin term or phrase. The objective is to provide a Technical Term Reference manual for non-English speaking students and engineers who are familiar with Mandarin, but uncomfortable with English and to provide a similar reference for English speaking students and engineers working in an area of the world where the Mandarin language predominates.